2018
DOI: 10.1016/j.scriptamat.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Materials selection for nuclear applications: Challenges and opportunities

Abstract: a b s t r a c t a r t i c l e i n f oWe discuss the challenge of selecting materials for nuclear applications and outline the need for comprehensive databases to assist scientists and engineers in choosing materials that meet interdependent physical, chemical, and nuclear criteria. In conventional engineering, chemical and physical properties and the electronic structure of materials are typically the primary considerations; nuclear applications must also consider the nuclear physics characteristics of a mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 35 publications
0
35
0
1
Order By: Relevance
“…In order to investigate the roughness of the YSZ thin film layer on the surface of SS316L substrateAFM-Atomic Force Microscope was employed. Figures 5 and 6 show the AFM topography analyses of the samples's surface (2 and 3 dimensions) for 7.2x10 4 and 14.4x10 4 number of shots, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to investigate the roughness of the YSZ thin film layer on the surface of SS316L substrateAFM-Atomic Force Microscope was employed. Figures 5 and 6 show the AFM topography analyses of the samples's surface (2 and 3 dimensions) for 7.2x10 4 and 14.4x10 4 number of shots, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thin films of YSZ (Ytrria-Stabilized Zirconia) ceramic have been successfully deposited on a SS316L austenitic stainless steel using Pulsed Laser Deposition (PLD) technique with the substrate temperature of 850°C and constant oxygen flow injection of 20 and 40 sccm that produce a chamber pressure of 60 and 200 mTorr for the numbers of laser shots 7.2×10 4 and 14.4×10 4 , respectively. The results showed that YSZ could homogeneously and sticky deposited on the surface of the SS316L surface with consist of homogeneous particles of YSZ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the service temperature of ultrasupercritical power plant will increase from the current level of 600°C to 700°C [1], some advanced nuclear energy systems will also operate at temperature between 600 to 700°C [2]. It is important to develop new grade high temperature steels for the core component application in these energy systems, as the strength of current applied steels cannot meet the service requirement if the operation temperature is higher than 600 to 650°C [3][4][5]. Especially, these advanced energy systems will use corrosive fluid, such as supercritical water, or liquid metal as coolant and thermal exchange medium.…”
Section: Introductionmentioning
confidence: 99%